THE EMPIRICAL RELATIONSHIP BETWEEN PRICE AND QUALITY OF RICE AT MARKET LEVEL IN WEST JAVA - Rachmat, Ridwan; Thahir, Ridwan; Gummert, Martin (Indonesian Journal of Agricultural Science, 2006)
Rice consumers in Indonesia exhibit wide preference variability and consumption patterns, largely because of the archipelagic nature of the country. Nowadays, the consumers become more discriminating on the rice quality due to the higher incomes and better life. Consumers are willing to pay higher price for specific quality. The objective of the study was to analyze relationship between price and grades of rice and consumer preference. The study was based on survey conducted from April 2004 to March 2005 at three-rice market centers representing a village market(Pasar Inpres) in Subang, district capital market (Pasar Johar) in Karawang, and rice center market (Pasar Induk Cipinang) in Jakarta, respectively. Parameters evaluated were changes in the quality and price of rice over time. The quality of the rice at each market was sampled monthly from two traders consisting three samples each. The rice quality was graded using existing local standar, i.e. grade 1, grade 2, and grade 3, and the price of each grade was recorded. The physical qualities of the rice samples such as moisture content, grain dimensions, percentage of whole kernels, grain color, and impurities/dockage (foreign matters, unhulled grains, and milled rice) were determined by ISO 950:1979 (for cereals-sampling as grain). Whereas the chemical qualities such as amylose and gelatinization were analyzed using Rapid Visco Analisis. The study showed that rice quality varied, most of them were long and slender kernels, chalkiness ranged between 10-20% (scale 5), and head ricearound 69-84%. The amylose content was intermediate (20-21%), the gelatinization temperature was high-intermediate (70-74oC), and the gel consistency was soft (65-70). The quality incentive, defined as theÂ  additional return assuming the quality level can be raised from grade 3 to grade 1, was up to Rp700 kg-1 (~25%). The price difference among markets could reach Rp630 kg-1 (~22%). The study indicated that rice color was the important parameter determining consumersâ preference,and consequently ditermining price difference. The correlation between the rice price and its grade was significant (R= 0.95).